2020
DOI: 10.1038/s41419-020-2597-7
|View full text |Cite
|
Sign up to set email alerts
|

Ginsenoside Rg3 promotes regression from hepatic fibrosis through reducing inflammation-mediated autophagy signaling pathway

Abstract: Inflammation and autophagy occur during hepatic fibrosis development caused by various pathogens, and effectively curbing of autophage may delay the occurrence of hepatic fibrosis. The current study aimed to unravel the inhibitory effects of Ginsenoside Rg3 (G-Rg3) on inflammation-mediated hepatic autophagy to curb hepatic fibrosis caused by thioacetamide (TAA)-induced subacute and chronic hepatic injury. TAA is mainly metabolized in the liver to cause liver dysfunction. After intraperitoneal injection of TAA … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
30
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 77 publications
(37 citation statements)
references
References 52 publications
1
30
0
Order By: Relevance
“…HY-10431, MedChem Express, Shanghai, China, 10 μΜ) ( Liu X. S. et al, 2019 ), a small molecular inhibitor, was used to inhibit the expression of TGF-β1, and Rapamycin (Cat No. HY-10219,MedChem Express, Shanghai, China, 100 nΜ) ( Liu X. et al, 2020 ) was used to inhibit the expression of mTOR. As shown in Figure 6A , the level of TGF-β1 in MNNG group increased significantly than control group.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…HY-10431, MedChem Express, Shanghai, China, 10 μΜ) ( Liu X. S. et al, 2019 ), a small molecular inhibitor, was used to inhibit the expression of TGF-β1, and Rapamycin (Cat No. HY-10219,MedChem Express, Shanghai, China, 100 nΜ) ( Liu X. et al, 2020 ) was used to inhibit the expression of mTOR. As shown in Figure 6A , the level of TGF-β1 in MNNG group increased significantly than control group.…”
Section: Resultsmentioning
confidence: 99%
“…Berberine shows a good therapeutic effect on ulcerative colitis (Jing et al, 2020) and can improve glucose metabolism and insulin resistance by suppressing the inflammatory response (Shan et al, 2020). Recent studies have shown that BBR also has anti-tumor effects, such as promoting autophagy, anti-proliferation, apoptosis and so on (Liu J. et al, 2020;Samadi et al, 2020). However, the therapeutic effect of BBR on MNNG-induced CAG and its potential mechanism is still unclear.…”
Section: Introductionmentioning
confidence: 99%
“…Total ginsenoside, an extensively studied ingredient that isolated from ginseng extract with 60% ethanol following Chinese Pharmacopoeia, is deemed to be one of the popular candidates for fibrosis-associated diseases. Moreover, individual ginsenosides isolated from total ginsenoside such as Rg 1 [ 62 65 ], Rb 1 [ 66 68 ], Re [ 69 ], Rg 3 [ 70 ], Mc 1 [ 71 ] also exert their anti-fibrosis potential (Fig. 2 ).…”
Section: Effects Of Ginseng Extract and Formulas On Ofdmentioning
confidence: 99%
“…Therapeutic properties of Panax ginseng C.A.Mey. such as anti-inflammatory, altering the composition and metabolism of the microbiota, ameliorating chronic inflammation, enhancing the immunity, resisting the oxidation again, and regulating the glucose and lipid metabolism have been widely reported ( Cao et al, 2019 ; Jang et al, 2019 ; Liu et al, 2019 , 2020 ; Xue et al, 2019 ; Huang et al, 2020 ; Quan et al, 2020 ; Xu et al, 2020 ). Intriguing new data suggest that Panax ginseng C.A.Mey.…”
Section: Introductionmentioning
confidence: 99%